Research on Architecture of Real-Time Satellite Remote Sensing System Based on Communication and Remote Sensing Integration - ZHAO Chenqian; YAN Ruidong; ZHAO Yun; LIU Yan; SUN Junshuai (天地一体化信息网络, 2025)
Traditional satellite remote sensing suffer from limited data transmission capabilities and lengthy business processes, making it difficult to meet the real-time acquisition demand of massive remote sensing data. The integration of satellite communication and remote sensing can enhance the transmission and processing capabilities of remote sensing, achieving real-time service. This article summarizes the development modes of communication and remote sensing integration, as well as their future evolution. From the perspective of balancing business integration and system integration, it studies the composition, deployment and functional architecture of real-time satellite remote sensing systems, as well as typical business processes such as remote sensing data relay, onboard data processing and task planning.